THE INFLUENCE OF LEARNING STYLE, LEARNING INTEREST, AND LEARNING ENVIRONMENT ON STUDENTS' LEARNING ACHIEVEMENT AT STATE VOCATIONAL SCHOOL, SOUTH JAKARTA - Nugroho, Dede Arfian Harsi; Zulaihati, Sri; Zakaria, Adam (International Journal of Multidisciplinary Research and Literature, 2024)
This research aims to determine the influence of Learning Style, Learning Interest, and Learning Environment on Learning Achievement in classes with an affordable population of 216 students from three schools, namely SMK Negeri 15 Jakarta, SMK Negeri 18 Jakarta, and SMK Negeri 20 Jakarta. The sample in this study amounted to 138 respondents using proportional random sampling techniques and the Isaac and Michael formula. The data collection method in this research uses a questionnaire method. This research uses data analysis techniques: descriptive analysis, analysis requirements testing, and hypothesis testing. This research shows a significant influence between learning style, learning interest, and learning environment on learning achievement; this is proven by the coefficient of determination value of 35.2%.